Pengaruh Jenis Asam dan Basa pada Pembentukan Senyawa Khitosan dari Limbah Kulit Rajungan - Oktafrina, Oktafrina; Marlina, Eulis (Jurnal Penelitian Pertanian Terapan, 2010)
The objective of this research was to known of acid and alkali effect to produced chitosan from rajungan husk. The implemented treatments were including deproteinization, demineralization and deasetylation treatments with several of acid and alkali. The deproteinization were conducted by 3-5 % NaOH and warm to 80o C than 2% HCl or H3PO4. Finally, chitosan produced by deasetylation with 30-40% NaOH. 100 gram substrates were produced 19% rendemen with deasetylation degree (DD) is 29,02%. Test of the chitosan at bakso and fish showed good condition until 48-50 hours. That is influenced by water activity of the materials. Keywords : rajungan husk, deproteinization, demineralization, deasetylation, chitosan